Exit Creek Water Surface Survey, June 2013 - Curran, Janet H. (ORCID: 000-0002-3899-6275); Long, Daniel A. (USGS Science Data Catalog, 2017)
This dataset consists of survey data from a longitudinal profile of water surface surveyed June 23-24, 2013 at Exit Creek, a stream draining Exit Glacier in Kenai Fjords National Park, Alaska. The survey was conducted using a total station at multiple instrument locations linked using visual estimates of instrument locations from an orthophoto. The intent of the survey was to provide detailed water surface elevations to compare to a 2012 digital elevation model.